Corrosion Resistance of 18Ni-300 maraging steel manufactured by LPBF. Issue 1 (August 2021) - Simson, T; Koch, J; Zetek, M; Zetková, I
Abstract: The study describes the corrosion behaviour of LPBF parts made of MAR 300 (EN 1.2709) in sulphuric acid. It includes the influence of the heat treatment on the part's properties as solution annealed and age hardened with reference to conventional samples. Laser remelted surfaces were examined as well. Due to the layered production of AM components, which is characteristic for this process, high surface roughness occurs. Therefore, for many applications and mostly on functional surfaces, complex post-processing of the surfaces is necessary. The reliable use of the manufactured components, demand knowledge of the specific influence of the selected post-processing methods on the electrochemical behaviour. The corrosion investigation takes place on different sample surfaces, such as milled, turned, sandblasted, untreated, grinded and laser-machined. The results show that there is no correlation between surface treatment and corrosion resistance. However, an increase in corrosion rate due to age hardening of the material can be observed for both LPBF and conventionally produced samples. By laser surface remelting of these age hardened samples, the corrosion resistance of these parts could be increased again, to the same level as in the solution annealed state.